ACUTE TRANSVERSE MYELITIS IN CHILDREN - Masood, Syed Asif; Ibrahim, Shahnaz (Journal of Ayub Medical College Abbottabad, 2006)
A case of Acute Transverse Myelitis (ATM) is presented. ATM is a rare disease in childhood. The diagnosis stems from the clinical presentation, cerebrospinal fluid findings, appearance of the spinal cord on imaging and ruling out differential diagnoses like Guillain-Barre syndrome (GBS) and Poliomyelitis. The proposed treatment is intravenous (IV) methyl prednisolone with variable chances of recovery. A controlled multicenter study is suggested to assess epidemiology, etiology and prognosis of ATM. Key Words: Transverse Myelitis, Sensory level, Methyl Prednisolone.